2019
DOI: 10.1038/s41598-019-53381-1
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low-loss and large-effective-area fiber for 100 Gbit/s and beyond 100 Gbit/s coherent long-haul terrestrial transmission systems

Abstract: Ultra-low-loss and large-effective-area fiber has been successfully applied in transoceanic transmission, which is considered as a promising candidate for 100 Gbit/s and beyond 100 Gbit/s coherent long-haul terrestrial optical networks. Several theoretical and experimental investigations have been reported, including provincial terrestrial field trial. To support long-haul terrestrial application, it is urgent to prove that the ultra-low-loss and large-effective-area fiber after terrestrial deployment can sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…In Figure 2b, the 13 C NMR spectrum of SP and SP‐D‐PU resin display several major signal peaks ascribed to carbonyl (155–180 ppm), aromatic (115–135 ppm), α‐carbon (45–67 ppm), β‐carbon (27–45 ppm), and methylene and methyl groups (13–27 ppm), which are in accordance with the results of Ma et al and Kang et al Compared to the pristine SP, the intensity of the peak at 116.6 ppm of the SP‐D‐PU resin nearly disappears due to the formation of hydrogen bonds between the catechol OH of D‐PU and the SP, while the increased peak intensity at 71.2 ppm (CHOH) further reflects the existence of additional interactions between the polyurethane and SP molecules . Moreover, the SP‐D‐PU resin exhibits a new peak at 145.2 ppm corresponding to the CN groups due to the Schiff base reaction between the catechol OH and NH 2 of SP . Furthermore, after the introduction of D‐PU elastomer, it is also found that several new peaks appear in the region of α‐carbon (64.6, 48.9, and 45.9 ppm) and β‐carbon (36.1 and 32.3 ppm), and the spectra between 27 and 30 ppm show a significant difference to the pristine SP.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…In Figure 2b, the 13 C NMR spectrum of SP and SP‐D‐PU resin display several major signal peaks ascribed to carbonyl (155–180 ppm), aromatic (115–135 ppm), α‐carbon (45–67 ppm), β‐carbon (27–45 ppm), and methylene and methyl groups (13–27 ppm), which are in accordance with the results of Ma et al and Kang et al Compared to the pristine SP, the intensity of the peak at 116.6 ppm of the SP‐D‐PU resin nearly disappears due to the formation of hydrogen bonds between the catechol OH of D‐PU and the SP, while the increased peak intensity at 71.2 ppm (CHOH) further reflects the existence of additional interactions between the polyurethane and SP molecules . Moreover, the SP‐D‐PU resin exhibits a new peak at 145.2 ppm corresponding to the CN groups due to the Schiff base reaction between the catechol OH and NH 2 of SP . Furthermore, after the introduction of D‐PU elastomer, it is also found that several new peaks appear in the region of α‐carbon (64.6, 48.9, and 45.9 ppm) and β‐carbon (36.1 and 32.3 ppm), and the spectra between 27 and 30 ppm show a significant difference to the pristine SP.…”
Section: Resultssupporting
confidence: 88%
“…The incorporated PU elastomer blue‐shifts the peak of SP at 1644–1650 cm −1 in the SP‐PU, as the newly formed intermolecular hydrogen bonds between the SP and PU partly break the intramolecular hydrogen bonds within the SP matrix . In addition, it is observed that a new peak appears at 1106 cm −1 , and the absorption intensities of the peaks around 1391 (COO bending) and 1446 cm −1 (NH blending) also increase, which all indicate that the PU induces crosslinking reactions and forms multiple hydrogen bonds with the SP molecules thus influencing the chemical environment of the SP functional groups . After incorporating the D‐PU elastomer, the intensity of the peaks at 1515, 1645, and 3278 cm −1 decrease, which is mainly because that the catechol OH of D‐PU further forms strong physical intermolecular interactions with the OH and amide groups of the SP molecules .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The solid content is a basic factor that affects adhesion performance during the curing process . If the solid content is too high, the adhesive is too thick to be mixed or spread for gluing.…”
Section: Resultsmentioning
confidence: 99%